Welcome :: Homework Help and Answers :: Mathskey.com
Welcome to Mathskey.com Question & Answers Community. Ask any math/science homework question and receive answers from other members of the community.

13,400 questions

17,804 answers

1,438 comments

39,711 users

simplify the expression

0 votes

√15(√6+6)

asked Jun 29, 2013 in PRE-ALGEBRA by rockstar Apprentice

1 Answer

0 votes

Given expression is √15(√6+6)

                               = √15(√6) + √15(6)

                               = √(15 * 6) + 6√15

                               = √(3*5*3*2) + 6√(3*5)            [Split into factors]

                               = 3√(5*2) + 6√(3*5)

                               = 3√5 ( √2 + 2√3)

                               = 3√5 [1.414 + 2(1.7320)]      [Since √2 = 1.414 and √3 = 1.7320]

                               = 3√5 [1.414 + 3.436 ]

                               = 3(2.2360)(4.878)                    [Since √5 = 2.2360]

                               = 32.7216

Therefore √15(√6+6) = 32.7216.

 

answered Jun 29, 2013 by joly Scholar

Related questions

asked May 9, 2014 in ALGEBRA 1 by anonymous
asked Nov 3, 2014 in ALGEBRA 1 by anonymous
...